Academic Labour, Digital Media and Capitalism (Combined PDF of all articles) - Thomas Allmer; Ergin Bulut (tripleC: Communication, Capitalism & Critique, 2018)
Combined pdf of all articles published in the special issue "Academic Labour, Digital Media and Capitalism", edited by Thomas Allmer and Ergin Bulut, tripleC: Communication, Capitalism & Critique 16 (1), 2018, pp. 44-240